Penegakan Hukum bagi Developer pada Kasus Dualisme Pengelolaan Rumah Susun : Studi Kasus Apartemen Mediterania Kemayoran - Febriana Parameswari Devi (Magister Kenotariatan Universitas Surabaya, 2024)
Flats are equipped with shared parts, shared land, and shared objects arranged by Association of Owners and Residents of Flats (P3SRS) as a legal entity. P3SRS should be facilitated by the developer. The main problem of this research, there is a dualism in the management of flats in the Mediterania Kemayoran Apartment between PPPSRS and the developer. This research aims to find out about the form of law enforcement for developers who do not want to hand over the management of flats to P3SRS and this causes cases of dualism in the management of flats. This research is normative juridical research with a conceptual and statutory approach. The results of the research conclude that in the regulations governing flats, there are no specific law enforcement provisions for developers and only emphasizes law enforcement for owners who do not form P3SRS, so the government needs to overcome this legal vacuum and provide protection for residents and/or owners of flats as long as cases of management dualism occur